Fiqh of Budgeting: Study of Management of the State Budget for People's Welfare in the Perspective of Maqâshid al-Shari'ah - Ahmad, Maghfur (al-'adalah, 2019)
The budget plays an important role, both in Islamic political fiqh discourse and in the national constitutional dictum. However, hegemony of capitalism has implications for the low state budget that is allocated to meet the needs of the poor. Budgeting policies are considered to be more in favor of the interests of investors than for the people welfare. This study aims to explore the repertoire of Islamic law in managing the state budget in a participatory manner for people's welfare. Through qualitative research, this study relies on library resources that contain management of the state budget in the budgetary fiqh narrative and the maqâshid al-shari'ah as the main basis of this literature study. The results of this study reveal that the state has an obligation to prosper the people. In a fiqh perspective, the mandate to serve people's needs require a participatory mechanism. Community participation in assessing the basic needs of the people can guarantee the state budget plan for effective and targeted development. In addition, the basic rights of citizens regarding education, economy, culture, law and politics are guaranteed as part of the implementation of the principles of the maqâshid al-shari'ah in the management of the state budget.